Arctic cooperation between Norway and Russia in healthcare delivery and emergency preparedness on Svalbard: barriers and facilitators - Wæhler, Turid Austin (Polar Geography, 2023)
This interdisciplinary study explores whether increased cooperation in healthcare delivery and emergency preparedness between Norway and Russia on the Arctic archipelago Svalbard may increase the quality of these services and whether cooperation is desired. Ten semi-structured interviews were conducted and the respondents were asked to describe the current cooperation. Further, they were questioned about what they considered the main facilitators and the main barriers to cooperation. By analyzing the results, the study explores these facilitators and barriers and identifies how healthcare delivery and emergency preparedness are organized on Svalbard. Moreover, the study detects potential areas of cooperation within the given field, and the desire for such cooperation. The findings show that there are both facilitators and barriers regarding cooperation in healthcare delivery and emergency preparedness. Main facilitators include mutual trust, shared challenges, and existing administrative structures, equipment, and infrastructure. The main barriers involve differences in language and culture, high personnel turnover, and divergent systems for emergency preparedness on the Norwegian and Russian mainland. Mine rescue, emergency preparedness, and joint exercises focusing on health challenges are areas where Norway and Russia may cooperate in the future.